Association of FoxP3/Scurfin Germline Polymorphism (C-2383T/rs3761549) with Colorectal Cancer - Zahra Mojtahedi (Shiraz University of Medical Sciences, 2013)
Background FoxP3 gene encodes a transcription factor with crucial roles in the development and function of regulatory T cells. Objectives The present study was conducted to investigate whether the C-2383T (rs3761549) polymorphism in the promoter region of the FoxP3 gene is associated with colorectal cancer. Patients and Methods The study groups consist of 108 patients (52 men and 56 women) with colorectal cancer and 187 (126 men and 61 women) healthy individuals. They were genotyped for the FoxP3 polymorphism at position -2383 C > T using polymerase chain reaction-restriction fragment length polymorphism method. Frequencies of the gene variants were analyzed separately in men and women since FoxP3 is an X-linked gene. Results The numbers of female patients with C/C, C/T and T/T genotypes were 48 (85.7%), 7 (12.5%) and 1 (1.8%), while in female controls, they were 53 (86.9%), 8 (13.1%) and 0 (0%), respectively. In male patients and controls, frequencies of the C genotype were 49 (94.2%) and 118 (93.7%), and the T genotype were 3 (5.8%) and 8 (6.3%), respectively. Genotype frequencies were not significantly different between controls and colorectal cancer patients. Distance metastasis was significantly associated with the FoxP3 polymorphism as calculated using Pearson’s chi-squared test (P = 0.006 in men and P = 0.03 in women). While 50% of metastatic patients had T or C/T (or T/T) genotype, the percentage of this genotype in non-metastatic patients was 4% in men and 11.5% in women. However, P values did not remain significant if differences were calculated using two-sided Fisher׳s exact test (P = 0.11 in men, and P = 0.09 in women); this might be due to the low number of our metastatic patients. Other characteristics of patients including age, tumor grade and stage were not significantly associated with the polymorphism. Conclusions Our results supported an association between C-2383T FoxP3 polymorphism and metastatic colorectal cancer in southern Iran.